Tracking the terrestrial hydroclimate and paleoclimate response to changes in atmospheric pCO₂ using stable oxygen and carbon isotopes: a proxy-model comparison across Cenozoic Eurasia - Driscoll, Elizabeth, author; Rugenstein, Jeremy Caves, advisor; Denning, Scott, committee member; Keys, Patrick, committee member; Ronayne, Michael, committee member (Colorado State University. Libraries, 2022)
Despite well-known constraints on the global hydrologic cycle with future warming, the response of the terrestrial hydrologic cycle – and hence future available freshwater resources – remains uncertain. This is largely due to the difficulty in predicting changes in environmental parameters such as precipitation (P), evapotranspiration (ET), and runoff (q). Shifts in the ratio of P/ET can be quantified using the δ18O of precipitation (δ18Op), given that P decreases δ18Op and ET increases δ18Op. Additionally, the δ13C composition of soil can provide insight into shifts in P and ET by recording the response of vegetation to changing climate. To better understand how the terrestrial water cycle will change with future warming, we utilize the geologic stable oxygen and carbon (δ18O and δ13C) isotope record to reconstruct past spatial distribution and longitudinal gradients of δ18Op and δ13C across Eurasia during periods of high atmospheric pCO2. We compile nearly 15,000 samples of authigenic carbonate and tooth enamel samples that span the Cenozoic Era across Eurasia. Oxygen isotopes in these proxies record the meteoric water δ18O signature during the time of mineral formation, which allows for reconstruction of moisture transport in the past. Soil carbonate δ13C, in turn, captures shifts in primary productivity and aridity, providing a complementary viewpoint to changes in the hydroclimate response to increased atmospheric pCO2. The δ18O record indicates that the westerlies have driven moisture transport across Eurasia since at least the Eocene. Additionally, steeper δ18Op gradients correspond with periods of high pCO2, suggesting a relatively high P/ET ratio and/or a higher evaporative fraction of ET, which preferentially supplies air parcels with 18O and thus steepens the gradient. The δ13C record demonstrates an increase in aridity in Asia during the late Cenozoic concurrent with stable (or slightly increased) primary productivity in Europe. Both isotopic records indicate that hydroclimate is driven predominantly by shifts in global climate due to changes in pCO2 and is only marginally impacted by dramatic changes in Cenozoic paleogeography. The proxy δ18Op gradients were compared to δ18Op gradients produced by both a simple reactive transport model and by an isotope-enabled earth system model. Gradients of δ18Op produced by both models under varying pCO2 demonstrate a mismatch between the proxy and model δ18O gradient response to CO2 – both models generate shallow gradients during periods of high pCO2 (4x Pre-Industrial pCO2) and generate the steepest gradients with the lowest pCO2 (Pre-Industrial pCO2). The proxy-model mismatch implies that these models may be misrepresenting the response of transpiration or the partitioning of P into ET and q at higher atmospheric CO2 concentrations.
Zip file contains compilation references.
Keywords: Eurasia; isotopes; Cenozoic; paleoclimate; hydroclimate